2017
DOI: 10.1186/s13068-017-0788-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-concentration n-caproic acid from lactate through fermentation using a newly isolated Ruminococcaceae bacterium CPB6

Abstract: Background n-Caproic acid (CA), as a medium-chain carboxylic acid, is a valuable chemical feedstock for various industrial applications. The fermentative production of CA from renewable carbon sources has attracted a lot of attentions. Lactate is a significant intermediate waste in the anaerobic breakdown of carbohydrates that comprise 18–70% of the chemical oxygen demand (COD) in municipal and some industrial wastewaters. Recently, researchers (including our own group) reported the CA production using lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
145
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(160 citation statements)
references
References 34 publications
13
145
2
Order By: Relevance
“…Even compared to strains that can produce CA from other substrates (e.g., ethanol, glucose, galactitol, etc), strain CPB6 showed the highest CA titer and very high productivity (comparable to the highest as reported so far) (Table 1). Additionally, the strain prefers initial pH-values of 5.0-6.5, and a temperature range 30-40°C for CA production (Zhu et al, 2017). These results indicated that strain CPB6 could be used as a powerful biocatalyst source for the biotechnological production of CA from lactate-containing waste streams.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Even compared to strains that can produce CA from other substrates (e.g., ethanol, glucose, galactitol, etc), strain CPB6 showed the highest CA titer and very high productivity (comparable to the highest as reported so far) (Table 1). Additionally, the strain prefers initial pH-values of 5.0-6.5, and a temperature range 30-40°C for CA production (Zhu et al, 2017). These results indicated that strain CPB6 could be used as a powerful biocatalyst source for the biotechnological production of CA from lactate-containing waste streams.…”
mentioning
confidence: 88%
“…Recently, we isolated a bacterial strain CPB6 from the CA-producing microbiome, and the isolate could produce 16.6 g/L of CA from lactatecontaining wastewater with a maximum production rate of 5.29 g/L/d (Zhu et al, 2017). The final CA titer of strain CPB6 was > 35-fold higher than that of M. elsdenii (Marounek et al, 1989) when lactate was used as the electron donor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The odd-chain valeric (C5) and heptanoic (C7) acids are products of reverse β-oxidation when the chain elongation process starts with propionyl-CoA. While there are demonstrations of this wide range of possible products from chain elongation (5, 18), and MCFA-bioreactors typically produce more than one product (4, 12, 14, 15, 19, 20), a strategy to control the final product length has not yet emerged. We are interested in obtaining the knowledge needed for the rational development and implementation of strategies to improve MCFA yields and control product formation in MCFA-producing microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…P. fermentans LDH clusters with proteins from organisms that consume lactate anaerobically ( Fig. 11 ), including two bacteria known to convert lactate to MCFA, Ruminococcaeae CPB6 and Megasphaera elsdenii (5, 7), and with the LDH from A. woodii that uses electron confurcation to couple lactate and ferredoxin oxidation with NAD + reduction to overcome the thermodynamic bottleneck of lactate oxidation (27). Pairwise correlation analyses of transcript abundance ( Fig.…”
Section: Resultsmentioning
confidence: 99%